Interactions between senescence and leaf orientation determine in situ patterns of photosynthesis and photoinhibition in field-grown rice - Murchie, Erik H.; Chen, Yi-zhu; Hubbart, Stella; Peng, Shaobing; Horton, Peter (Oxford University Press, 1999)
Photosynthesis and photoinhibition in field-grown rice (Oryza sativa L.) were examined in relation to leaf age and orientation. Two varieties (IR72 and IR65598-112-2 [BSI206]) were grown in the field in the Philippines during the dry season under highly irrigated, well-fertilized conditions. Flag leaves were examined 60 and 100 d after transplanting. Because of the upright nature of 60-d-old rice leaves, patterns of photosynthesis were determined by solar movements: light falling on the exposed surface in the morning, a low incident angle of irradiance at midday, and light striking the opposite side of the leaf blade in the afternoon. There was an early morning burst of CO2 assimilation and high levels of saturation of photosystem II electron transfer as incident irradiance reached a maximum level. However, by midday the photochemical efficiency increased again almost to maximum. Leaves that were 100 d old possessed a more horizontal orientation and were found to suffer greater levels of photoinhibition than younger leaves, and this was accompanied by increases in the de-epoxidation state of the xanthophyll cycle. Older leaves had significantly lower chlorophyll content but only slightly diminished photosynthesis capacity.